2014
DOI: 10.5482/hamo-13-08-0041
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for arterial and venous thrombotic disorders

Abstract: SummaryThe haemostatic system maintains the blood in a fluid state, but allows rapid clot formation at sites of vascular injury to prevent excessive bleeding. Unbalances within the haemostatic system can lead to thrombosis. Inspite of successful research our understanding of the disease pathogenesis is still incomplete. There is great hope that genetic, genomic, and epigenetic discoveries will enhance the diagnostic capability, and improve the treatment options. During the preceding 20 years, the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 150 publications
0
4
0
2
Order By: Relevance
“… 45–48 So far, a number of VTE biomarkers have been proposed in addition to or together with D-dimer, including CRP, sP-Sel, FVIII, tissue factor-positive microparticles and leucocytes as promising candidates. 27 35 39 49–51 The validity of these markers remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“… 45–48 So far, a number of VTE biomarkers have been proposed in addition to or together with D-dimer, including CRP, sP-Sel, FVIII, tissue factor-positive microparticles and leucocytes as promising candidates. 27 35 39 49–51 The validity of these markers remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…While genetic predisposition to arterial thrombosis is increasingly understood [ 1 ], the knowledge of environmental modifiers contributing to cardiovascular disease (CVD) progression and arterial thrombosis remains elusive [ 2 ]. One of the environmental factors affecting arterial thrombus growth is the commensal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized and demonstrated that the expression of proteins involved in the haemostatic balance (such as tissue factor, α 2 β 1 integrin) can be modulated by genetic polymorphisms . The association between such polymorphisms and increased risk of venous or arterial thrombosis was evaluated by several studies, but results were not always consistent . On the contrary, the association between increased risk of bleeding and genetic polymorphisms of proteins involved in haemostatic processes was not evaluated, except after heart surgery.…”
Section: Introductionmentioning
confidence: 99%